2020
DOI: 10.1007/s00467-020-04555-x
|View full text |Cite
|
Sign up to set email alerts
|

Consensus recommendations for the care of children receiving chronic dialysis in association with the COVID-19 epidemic

Abstract: Coronavirus disease 2019 (COVID-19) has rapidly spread not only in China but throughout the world. Children with kidney failure (chronic kidney disease (CKD) stage 5) are at significant risk for COVID-19. In turn, a set of recommendations for the prevention and control of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and COVID-19 in pediatric hemodialysis (HD) centers and in home peritoneal dialysis (PD) settings have been proposed. The recommendations are based on the epidemiological featur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
86
0
12

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(98 citation statements)
references
References 8 publications
0
86
0
12
Order By: Relevance
“…The ward managers need to assign medical staff to isolation wards according to national standards 14 26 or to the severity of patients' conditions 31 to ensure adequate human resources. 34 Thus, to ensure adequate rest 34 for staff, rotation every half month 26 31 or 1 month 20 is recommended. In addition, it was suggested that the managers relay the latest knowledge of COVID-19 34 and disease-related nosocomial infection prevention and control training 14 21 26 to all medical staff.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The ward managers need to assign medical staff to isolation wards according to national standards 14 26 or to the severity of patients' conditions 31 to ensure adequate human resources. 34 Thus, to ensure adequate rest 34 for staff, rotation every half month 26 31 or 1 month 20 is recommended. In addition, it was suggested that the managers relay the latest knowledge of COVID-19 34 and disease-related nosocomial infection prevention and control training 14 21 26 to all medical staff.…”
Section: Discussionmentioning
confidence: 99%
“…Level II protection is required in special departments, such as the infectious disease department 10 and the in-centre haemodialysis department. 34 Special procedures: personal protection management 11. For personal protection management during special procedures that could produce aerosols, no less than level II protection 10 14 20 25 38 or perhaps level III protection 15 chlorine-containing solution should be used to spray the outside of waste bags, 14-16 20 and disinfection should be performed for >10 min 14-16 20 before transport.…”
Section: Content Summary and Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…While most studies of COVID-19 in children have found an increased rate of hospitalisation and intensive care unit (ICU) admission in children with comorbidities [5,13,14], some studies did not nd a difference in admission rates in children with underlying chronic health conditions [15]. It has been hypothesised that children with chronic kidney disease have an elevated risk for the acquisition of COVID-19 due to their immunocompromised state and frequent exposure to the hospital setting [16]. While an increased rate of Kawasaki-like multi-system in ammatory disease has been reported among children with COVID-19 [17], it is still unclear if patients with immunode ciency or immunomodulatory treatment are at higher risk.…”
Section: Introductionmentioning
confidence: 99%